Dual‐responsive reversible photo/thermogelling polymers exhibiting high modulus change. Issue 18 (24th June 2016) - Dou, Qingqing; Liow, Sing Shy; Weng, Wengui; Loh, Xian Jun
Abstract : This work describes the synthesis of a novel photo‐thermogelling polymer which exhibits a high change in modulus upon UV irradiation. The sol‐to‐gel transition is reversible and can be achieved by exposure to sunlight or light at higher wavelengths.